A study on the benefits of practical training for undergraduate students - Abdullah, Kalthom; Ismail, Yusof; Mhd Sarif, Suhaimi (Research Centre, 2003)
The purpose ofthis study is to find out the students' opinion regarding the benefits ojpractical training If the students find that practical training is beneficial to them, the researchers would like to find Olit in what ways they are beneficial, and ifnot, what are the alternatives